Constituents of the stem and root essential oils of Kadsura heteroclita (Roxb.) Craib from Vinh Phuc province - Thanh, Bui Van; Ban, Ninh Khac; Dai, Do Ngoc (Academia Journal of Biology, 2012)
The stem and root essential oils of Kadsura heteroclita (Roxb.) Craib were prepared by steam distillation of fresh materials in a glass for 3h. The essential oils yields were 0.37% and 0.30% from the roots and stems (in absolute dry material), respectively. The stem and root essential oils from Kadsura heteroclita (Roxb.) Craib analyzed by GC and GC/MS showed 26 constituents and 41 constituents identified in the stem and root essential oils, respectively. The major components of the root essential oil of Kadsura heteroclita are: epi-bicyclogermacrene (19.6%), terpinolene-4-ol (13.3%), d-cadinene (8.9%) and spathulenol (7.7%). The major components of the stem essential oil of Kadsura heteroclita are: terpinolene-4-ol (22.4%), bicyclo[4.4.0]dec-1-ene (18.9%), d-cadinene (8.8%), a-cadinol (6.2%) and cadina-1,4-diene (6.0%). Most of major components of root and stem essential oils extracted from Kadsura heteroclita are similar, such as, terpinolen-4-ol (13.3% in roots and 24,4% in stems), d-cadinen (8.9% in roots and 8.8% in stems), a-copaen (3.7% in root and 3.8% in stems), a-cadinol (4.2% in roots and 6.2% in stems). But the major component in the stem oil as epi-bicyclogermacren (19.6%) did not appear in the root oil; while the bicyclo [4.4.0] dec-1-en (18.9%) only found in the root oil of K. heteroclita. The major constituents of the stem essential oils of Kadsura heteroclita (Roxb.) Craib from Vietnam and China are extremely variable.